Persistent hepatitis C virus infections and hepatopathological manifestations in immune-competent humanized mice - Chen, Jizheng; Zhao, Yang; Zhang, Chao; Chen, Hairong; Feng, Jin; Chi, Xiumei; Pan, Yu; Du, Jun; Guo, Min; Cao, Huang; Chen, Honghe; Wang, Zilong; et al. (Cell research, 2014)
The majority of hepatitis C virus （HCV） infection develops chronic infection, which causes steatosis, cirrhosis and hepatocellular carcinoma. However, understanding HCV chronicity and pathogenesis is hampered by its narrow host range, mostly restricted to human and chimpanzee. Recent endeavour to infect a variety of humanized mice has not been able to achieve persistent HCV infection unless the essential innate immune responsive genes are knocked out. Nevertheless, such immune-compromised humanized mice still lacked HCV infection-induced hepatopathogenesis. Here we report that transgenic mice in ICR background harboring both human CD81 and occludin genes （C/O^Tg） are permissive to HCV infection at a chronicity rate comparable to humans. In this mouse model, HCV accomplishes its replication cycle, leading to sustained viremia and infectivity for more than 12 months post infection with expected fibrotic and cirrhotic progression. Host factors favorable for HCV replication, and inadequate innate immune-response may contribute to the persistence. Lastly, NS3/4 protease inhibitor telaprevir can effectively inhibit de novo RNA synthesis and acute HCV infection of C/O^Tg mice. Thus, chronic HCV infection with complete replication cycle and hepatopathologic manifestations is recapitulated, for the first time, in immune-competent mice. This model will open a new venue to study the mechanisms of chronic hepatitis C and develop better treatments.